Saxony - economic characteristics and relations with the Czech Republic - Hrančík, Přemek; Jiránková, Martina, 1967-; Jelínek, Tomáš; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2010)
The first chapter of this bachelor thesis deals with general characteristics of the Saxony region and provides basic information about the country, its political system, state administration and about Saxony's position in the EU. The second part contains synoptic analysis of the local economy by selected economic indicators, which demonstrate changes in the economic development of the Free State of Saxony in the past recent years. The work also deals with comparison of Saxony with other federal states in the Federal Republic of Germany. The third part focuses on cross-border cooperation, which was enhanced by access of the Czech Republic into the European Union's structures.
Vedoucí práce: Martina Jiránková
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2010
Rok obhajoby 2010
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses